The injustice of the goddess Ishtar in ancient Iraqi literature - Fahad , Mohammed (Journal of College of Education, 2020)
Religion, in all its aspects and its constituents, occupied a prominent place in the life of ancient Iraqis, which is evidenced by the abundance of religious codes and texts left by the Iraqi civilization, whether it was news of the rulers and kings of their activities by constructing various temples and establishing various religious rites, And from the many cuneiform texts in the Sumerian and Akkadian languages about religious life, confirms the belief of the ancient Iraqis that their gods have qualities that are the same as those of humans, except that they differ from them only in immortality and supernatural abilities, It was difficult for humans to know their goals, but they were also getting sick and on the verge of death, and they were also fighting and being killed or wounded. The inhabitants of ancient Iraq also believed that their deities had very human characteristics, some of the gods were warlike, while others were friendly and some were working hard, others were lazy. Based on the foregoing, the topic of our research entitled (The injustice of the goddess Ishtar to the other gods) was chosen, which consists of three axes. The first axis deals with the injustice of the goddess Ishtar to her sister, the goddess Ershkigal, and the second axis deals with the injustice of Ishtar to her husband Damuzi. The third axis dealt with her injustice to the god Enki, and in each axis we mentioned how the gods reacted to the injustice imposed on them by Ishtar.